Trajectories of daily antipsychotic use and weight gain in people hospitalized for the first episode of psychosis - Kristyna Vochoskova; Sean R. McWhinney; Marketa Fialova; Marian Kolenic; Filip Spaniel; Petra Furstova; Petra Boron; Yurai Okaji; Pavel Trancik; Tomas Hajek (European Psychiatry, 2024)
Abstract